Variabilidade da frequência cardíaca, funções cognitivas e nível de atividade física em pacientes com doença de Alzheimer - Túbero, Grazieli Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Alzheimer's disease (AD) is the most common kind of dementia in world. In this disease occur changes in the Central Nervous System (CNS) and some studies also show changes in the Autonomic Nervous System (ANS). One way most effective to evaluate the ANS is with of heart rate variability (HRV). This assessment describes the RR intervals (iR-R) that can measure the modulation of ANS. Besides that, some studies indicate that there relationship between cognitive functions, level of physical activity and heart rate variability in healthy subjects. Despite there this regard, studies with patients with AD have focused more on cardiac autonomic modulation. The aim of this study was to compare the behavior of cardiac autonomic modulation through the HRV in the supine and orthostatic postures in patients with AD and cognitively preserved elderly and also correlate cognitive functions and level of physical activity with HRV in patients with AD. Participated in this study 17 patients with AD and 14 cognitively preserved elderly while making use of their regular medications. HRV was measured in both groups in supine and orthostatic postures, ten minutes each position. Sequences of 256 RR intervals were analyzed through linear of (spectral analysis - low frequency (LF) and high frequency (HF) in normalized units and absolute units] and non-linear methods [symbolic analysis - 0V%, 1V%, 2UV%, 2VD%, Shannon entropy (SE), conditional entropy (normalized complexity index - NCI)]. To assess the global cognitive function in cognitively preserved elderly was used the Mini Mental State Examination (MMSE) and to measure the level of physical activity was utilized the Baecke Questionnaire Modified for the Elderly (BQME). For patients with AD the same instruments were performed and also were applied Verbal Fluency Test (VFT) and Clock Drawing Test (CDT). The independent test t showed significate differences between groups in symbolic indices (2VS% (p=0.00)...

A doença de Alzheimer (DA) é a forma mais comum de demência no mundo. Nesta doença ocorrem alterações no Sistema Nervoso Central (SNC) e alguns estudos apontam, também, alterações no Sistema Nervoso Autônomo (SNA). Uma das formas mais eficaz de se avaliar o SNA é por meio da variabilidade da frequência cardíaca (VFC). Essa avaliação descreve os intervalos R-R (iR-R) que podem mensurar a modulação do SNA. Além disso, alguns estudos apontam que há relação entre funções cognitivas, nível de atividade física e VFC em indivíduos saudáveis. Apesar de haver essa relação, os estudos com pacientes com DA focaram mais na modulação autonômica cardíaca. O objetivo deste estudo foi comparar o comportamento da modulação autonômica cardíaca por meio da VFC na posição supina e ortostática em pacientes com DA e idosos preservados cognitivamente, e também correlacionar funções cognitivas e nível de atividade física com a VFC nos pacientes com DA. Participaram do estudo 17 pacientes com DA e 14 idosos preservados cognitivamente que faziam uso de seus medicamentos habituais. A VFC foi coletada em ambos os grupos na postura supina e ortostática, sendo10 minutos em cada posição. Foram selecionados trechos de 256 intervalos R-R para as análises lineares da VFC [análise espectral - baixa frequência (BF) e alta frequência (AF) em unidades normalizadas e absolutas], e método não lineares [análise simbólica - 0V%, 1V%, 2VS% e 2VD%, entropia de Shannon (ES), entropia condicional (índice de complexidade normalizado - ICN)]. Para avaliar as funções cognitivas globais nos idosos preservados cognitivamente foi utilizado o Mini Exame do Estado Menta (MEEM) e para mensurar o nível de atividade física foi utilizado o Questionário Baecke Modificado para Idosos (QBMI). Para os pacientes com DA foram utilizados os mesmos instrumentos e foram aplicados também o teste de Fluência Verbal (FV) e Teste do Desenho do Relógio...
Keywords: Physical education and training; Educação fisica; Alzheimer, Doença de; Variabilidade do batimento cardíaco; Cognição na velhice; Exercícios físicos para idosos